(3CKQ GdSjGSGJ GdeGdjI GdTQYjI aj JMbjb GdJhGRf GdeGdi GdYGe aj GdOhdI GdMOjKI (B:s (3OQGSI ebGQfI (B/s - (3GdWhGHi, eMeO Mdeis ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2008)
(3eaghe GdSjGSI GdeGdjI aj GdacQ GdhVYj hGdSjGSI GdTQYjI(B- (3GdVhGHW GdTQYjI hGdbGfhfjI dJMbjb GdJhGRf GdeGdj GdYGe(B- (3eSGgeI GdUObGJ aj JMbjb GdJhGRf GdeGdj GdYGe(B- (3GdJhGRf GdeGdj GdYGe heOi MQjI JONd GdOhdI aj GdfTGW GdEbJUGOj(B- (3eOi JcGed GdSjGSGJ GdeGdjI dJMbjb GdJhRGf GdeGdj(B- (3CKQ GdSjGSI GdeGdjI aj JMbjb GdJhGRf GdeGdj GdYGe(B- (3CKQ GdSjGSI GdTQYjI aj JMhjd GdJfejI HWQjb GdEUOGQ GdfbOj hGdEFJeGf GdeUQajs
(3GdeQGLY U(B.347s
Keywords: (3GdEOGQI GdeGdjIs; (3GdJhGRf GdeGdjs; (3GdSjGSI GdeGdjIs